2022
DOI: 10.1002/mco2.96
|View full text |Cite
|
Sign up to set email alerts
|

Low hemoglobin is associated with worse outcomes via larger hematoma volume in intracerebral hemorrhage due to systemic disease

Abstract: Whether hemoglobin is associated with outcomes of a specific subtype of intracerebral hemorrhage (ICH) is unknown. A total of 4643 patients with ICH from a multicenter cohort were included in the analysis (64.0% male; mean age [SD], 58.3 [15.2] year), of whom 1319 (28.4%) had anemia on admission. The unsupervised consensus cluster method was employed to classify the patients into three clusters. The patients of cluster 3 were characterized by a high frequency of anemia (85.3%) and mainly composed of patients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Elevated Tf level in response to iron deficiency may be the adoptive mechanism after anemic/hypoxic injury. Hemoglobin (Hb) is the iron‐containing oxygen‐transport metalloprotein in the red blood cells that is vital for oxygen supply in the brain (Zhang, Shu, Chen, et al, 2022), and higher Hb level was associated with increased mortality and disability in ischemic stroke patients (Zhang, Shu, Li, et al, 2022). However, in iron deficiency conditions, the suppression of Hb and red blood cell levels also leads to an anemic/hypoxic state, which induces hypoxia‐inducible factor‐1 (HIF‐1) expression (Rolfs et al, 1997).…”
Section: The Role Of Iron In Ischemic Strokementioning
confidence: 99%
“…Elevated Tf level in response to iron deficiency may be the adoptive mechanism after anemic/hypoxic injury. Hemoglobin (Hb) is the iron‐containing oxygen‐transport metalloprotein in the red blood cells that is vital for oxygen supply in the brain (Zhang, Shu, Chen, et al, 2022), and higher Hb level was associated with increased mortality and disability in ischemic stroke patients (Zhang, Shu, Li, et al, 2022). However, in iron deficiency conditions, the suppression of Hb and red blood cell levels also leads to an anemic/hypoxic state, which induces hypoxia‐inducible factor‐1 (HIF‐1) expression (Rolfs et al, 1997).…”
Section: The Role Of Iron In Ischemic Strokementioning
confidence: 99%
“…106 Indeed, cohort studies have reported an inverse relationship between admission Hb level and initial ICH volume and the risk for subsequent hematoma expansion. 97,[107][108][109] In a recent meta-analysis where the data of 4172 ICH patients from 2 multicenter RCTs and 1 multicenter prospective observational study were individually analyzed, admission anemia was associated with increased risk for poor outcome (OR, 1.49; 95% CI, 1.17-1.89; P = .001; I 2 = 0%). 110 Interestingly, in a recent prospective observational cohort of 917 ICH patients, Roh et al 111 reported an association between higher Hb level and the presence of diffusion-weighted imaging ischemic lesions, suggesting that there may exists a U-shape association between Hb level and outcome in ICH patients.…”
Section: Intracerebral Hemorrhagementioning
confidence: 99%
“…Compared with admission parameters, recent studies indicate that a nadir value (e.g., albumin and hemoglobin levels), which might better reflect the severity of the acute event, has a stronger correlation with clinical outcomes. For example, low nadir albumin levels, evaluated based on the lowest point during hospitalization rather than at admission, were associated with an increased risk of acute worsening of renal function [7][8][9]. The trend of the nadir levels of serum sodium and potassium during hospitalization tends to represent their average levels, which in turn reflect the comprehensive impact during hospitalization, including the acute phase of ischemic stroke and other potential influencing factors, thereby endowing them with predictive value.…”
Section: Introductionmentioning
confidence: 99%